Thérèse, êxtase de um corpo ofertado: travessia mitodológica de uma artista de f(r)icção - Silva, Karla Lidiane Costa Martins (2017)
This dissertation, entitled Thérèse, ecstasy of an offered body: the mythodological journey of a f(r)iction artist, travels over the grounds of art and holiness, discussed here by means of a practical/theoretical research embraced by the artist-researcher Karla Martins about her guide-myth: Saint Therese of the Child Jesus. The French saint, also known as the Holy Face, manifests itself in this investigation through the scope of the artist-researcher’s personal mythology and unveils herself through a performative experience. In order to carry such experience on, the research was based on the Mythodology in Art and the Artethnography, practices/concepts upheld by Prof. Ph.D. Luciana Lyra (UERJ), which, in turn, are connected to the fields of Anthropology of Experience (Anthropology of Performance), led by anthropologist Victor Turner, and Anthropology of the Imaginary, led by sociologist Gilbert Durand, which by their turn involve rites of passage, image, myth and ritual. The application of these mythodological procedures cause the most intimate of the artist-researcher’s pulsions to erupt and pervade her writing, as well as the creation of the performance Thérèse itself.